Praktik Sanggal pada Masyarakat Desa Blambangan Kecamatan Buay Runjung Kab. OKU Selatan - Cholidi Cholidi (Pusat Penelitian dan Penerbitan Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Islam Negeri Raden Fatah Palembang, 2015)
This research paper examines the mortgage done by Blambangan villagers in OKU Selatan. Furthermore, Islamic law regarding its practice is also discussed. It can be summarized that the mortgage there has a very low level of intensity. It is caused by three factors. First, the urgent needs of the people make the practice happen. Even if that happens, they try as hard as possible to borrow money from creditors who do not require any collateral. Second, there is a negative value for those who do the mortgage for the sake of borrowing money to meet their daily needs. Third, the creditors generally want valuable goods from the mortgage such as rubber plantations and rice fields in order that they can take advantage from the mortgaged things. Basically, the underlying principle of mortgage in Blambangan village of OKU Selatan is empowerment. However, the mortgage usually happens due to the desire to gain advantage over the troubles of others. The contract used in their mortgage is al-rohn.